A companion to Terence - Augoustakis, Antony.; Traill, Ariana, 1969-; Thorburn, John E. (Blackwell companions to the ancient world ;, 2013)
"A Companion to Terence offers the first comprehensive collection of essays on Terence in English. It includes a detailed study of Terence's plays, situating them in their socio-historical context and exploring their reception from the Classical through late antiquity, the Middle Ages, the Renaissance, to present day literature and performance. Each chapter discusses key issues in Terence, including Terence's relationship with his Greco-Roman models, his language and style, the question of performance and dramatic technique, and the socio-political background that shapes the themes, characters, structures, and cultural-political concerns. A Companion to Terence is a useful research tool for the growing number of scholars, students and critics of Terence and Roman comedy"--